CYBERBULLYING ANAK AKIBAT OVERSHARENTING DIGITAL: BATASAN OTORITAS PERWALIAN PERSPEKTIF MAQASHID SYARI’AH - Endiana Silviani (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2026)
This study aims to reconstruct the boundaries of parental guardianship rights over children's privacy in the digital space based on the Maqashid Sharia perspective. Using a qualitative socio-legal method, a conceptual approach, and netnography, this study observes three YouTube accounts of public figure families ("AH", "RO", "LE"). The results show that oversharenting practices, which expose children's physical and developmental vulnerabilities, are proven to trigger cyberbullying, ranging from baby shaming to milestone shaming. From Imam Al-Shatibi's Maqashid Sharia perspective, this parental digital negligence clearly violates Maqashid Sharia aspects, including Hifdz al-Nafs (protection of life), Hifdz al-Aql (protection of intellect), and Hifdz al-Nasl (protection of lineage), by generating long-term cyber trauma. In conclusion, parental guardianship and custody are not absolute rights but a fiduciary duty that must adhere to the child's best interests.